2007
DOI: 10.1055/s-2007-991515
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Microvasculature in Liver Injury

Abstract: Injury to the hepatic microvasculature, the hepatic sinusoids, manifests in several ways. The sinusoidal endothelial cells (SECs) may lose porosity and scavenger function (capillarization); SECs may loosen from their tetherings to the space of Disse or even detach completely (ischemia-reperfusion injury, early sinusoidal obstruction syndrome, peliosis hepatis, early acetaminophen toxicity); the space of Disse may be completely denuded of sinusoidal lining cells that then embolize and obstruct the sinusoid (ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
123
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(135 citation statements)
references
References 95 publications
(136 reference statements)
8
123
0
4
Order By: Relevance
“…This correlates directly with the histologic features of human SOS where a significant proportion of patients develop centrilobular perisinusoidal and vein occlusive fibrosis (1,2,4,15,40). In the animal model deposition of collagen in the sinusoids also occurs, albeit as late event (18), when activated, HSC acquire a myofibroblastic phenotype and are essential actors in hepatic fibrosis (41) as underlined by the diffuse perisinusoidal aSM actin expression (1).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This correlates directly with the histologic features of human SOS where a significant proportion of patients develop centrilobular perisinusoidal and vein occlusive fibrosis (1,2,4,15,40). In the animal model deposition of collagen in the sinusoids also occurs, albeit as late event (18), when activated, HSC acquire a myofibroblastic phenotype and are essential actors in hepatic fibrosis (41) as underlined by the diffuse perisinusoidal aSM actin expression (1).…”
Section: Discussionmentioning
confidence: 84%
“…SOS is morphologically characterized by centrilobular sinusoidal congestive dilatation and perisinusoidal hemorrhage, occasionally associated with perisinusoidal fibrosis and/or centrilobular hepatic vein fibrotic obstruction, nodular regenerative hyperplasia, or peliosis (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Bone marrow transplantation, alcoholic liver insults, and other chemical offenses may result in sinusoidal obstructive syndrome (SOS) or veno-occlusive disease, which is characterized by congested LSs, fibrin deposition, subendothelial edema, and hepatocellular abnormalities. 11,12 Evidence has shown that damage of LSECs is an initial step leading to SOS.…”
mentioning
confidence: 99%
“…It is histologically characterized by blood-filled cystic spaces that are continuous with hepatic sinusoids [1,2]. Although the pathogenesis of PH is not well known, it is frequently associated with tuberculosis, malignancy (such as hepatocellular carcinoma), acquired immunodeficiency syndrome (AIDS), and drugs (including steroids and oral contraceptives) [3][4][5][6][7][8][9][10][11][12]. Given its benign nature, asymptomatic PH does not require treatment.…”
Section: Introductionmentioning
confidence: 99%